2017
DOI: 10.1021/acs.langmuir.7b00098
|View full text |Cite
|
Sign up to set email alerts
|

Pd–M/C (M = Pd, Cu, Pt) Electrocatalysts for Oxygen Reduction Reaction in Alkaline Medium: Correlating the Electronic Structure with Activity

Abstract: The increasing global needs for clean and renewable energy have fostered the design of new and highly efficient materials for fuel cells applications. In this work, Pd-M (M = Pd, Cu, Pt) and Pt nanoparticles were prepared by a green synthesis method. The carbon-supported nanoparticles were evaluated as electrocatalysts for the oxygen reduction reaction (ORR) in alkaline medium. A comprehensive electronic and structural characterization of these materials was achieved using X-ray diffraction, high-resolution tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 58 publications
0
24
0
Order By: Relevance
“…The K-L plots show a linear behavior of the inverse of the current density with the reciprocal of the square root of the rotation speed. By applying the Levich equation [61] to the linear fitting of the experimental data, from the slope (B) we calculate the transferred electron number (n). The diffusion coefficient of oxygen in the electrolyte (D), the cinematic viscosity of the electrolyte (ν), and the bulk concentration of oxygen in the electrolyte (C*) are taken from Ref.…”
Section: Resultsmentioning
confidence: 99%
“…The K-L plots show a linear behavior of the inverse of the current density with the reciprocal of the square root of the rotation speed. By applying the Levich equation [61] to the linear fitting of the experimental data, from the slope (B) we calculate the transferred electron number (n). The diffusion coefficient of oxygen in the electrolyte (D), the cinematic viscosity of the electrolyte (ν), and the bulk concentration of oxygen in the electrolyte (C*) are taken from Ref.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, it can be observed that over a large potential interval in Figure 7 a), the mass activity of Pd-CeO 2-NR /C is higher than that of Pd/C. Even more, Figure 7 b) shows that despite the presence of the oxide, which may have induced a screening effect on Pd nanoparticles, [49] the specific activity of Pd-CeO 2-NR /C is also higher over the potential range studied. From the results evaluated so far, by comparing the behavior of Pd-CeO 2-NR /C and Pd/C before ADT, the former has the same value of E 1/2 as that of the monometallic.…”
Section: Evaluation Of Catalytic Activity For the Orrmentioning
confidence: 89%
“…Studying and developing Pd‐based catalysts is useful in theory and application. Many innovative approaches have been reported for the rational design and synthesis of Pd‐based alloys nanoparticles (NPs) with controlled shape, size, composition, and atomic arrangement . Among these strategies, forming alloys of Pd and transition metal (Fe, Co, Ni, and Cu) is a common approach to improve catalytic performance and stability.…”
Section: Introductionmentioning
confidence: 99%